2021
DOI: 10.1097/jpn.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

NICU-Specific Stress Following Traumatic Childbirth and Its Relationship With Posttraumatic Stress

Abstract: This mixed-methods pilot study investigated maternal perceived stress specific to infant neonatal intensive care unit (NICU) hospitalization as a moderator of the relationship between traumatic childbirth appraisal and symptoms of posttraumatic stress disorder (PTSD). NICU mothers (N = 77) were recruited via social media 1 to 4 months postpartum for a cross-sectional survey about perinatal experiences. Measures included traumatic childbirth, PTSD Checklist for DSM-5, and Parental Stressor Scale (PSS): NICU. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Eleven studies, published in 14 records, involved mothers and fathers; 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 one study involved fathers only [60] and the remaining 23 studies, reported in 26 records, involved mothers. 27 , 28 , 30 , 31 , 32 , 34 , 38 , 39 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies, published in 14 records, involved mothers and fathers; 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 one study involved fathers only [60] and the remaining 23 studies, reported in 26 records, involved mothers. 27 , 28 , 30 , 31 , 32 , 34 , 38 , 39 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 …”
Section: Resultsmentioning
confidence: 99%
“…Clinical interview was used in two studies, 46 , 54 clinical review of self-report scales was used in one study, published in three records, 38 , 39 , 62 and self-report scales were used in 32 studies, published in 36 records. 27 , 28 , 30 , 31 , 32 , 34 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 65 , 66 , 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 Seven different self-report scales were used, most commonly the Perinatal Post-traumatic Stress Disorder Questionnaire (PPQ). Cut-off points varied across studies, even when the same measure was used.…”
Section: Resultsmentioning
confidence: 99%
“…Of them, 56 studies were excluded according to the inclusion and exclusion criteria. A total of nine studies [22][23][24][25][26][27][28][29][30] were included in the final analysis (Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…This systematic review included one cohort study [22] and eight cross-sectional studies [23][24][25][26][27][28][29][30] with 3,821 postpartum women. A total of 1,823 with traumatic birth and 353 with postpartum PTSD were included in the final analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation